PAK1 Expression in Pancreatic Cancer: Clinicopathological Characteristics and Prognostic Significance. (February 2019) - Symeonidis, Nikolaos; Lambropoulou, Maria; Pavlidis, Efstathios; Anagnostopoulos, Constantinos; Tsaroucha, Alexandra; Kotini, Athanasia; Nikolaidou, Christina; Kiziridou, Anastasia; Simopoulos, Constantinos
Background: Improvement of the management of pancreatic cancer requires a better understanding of the genetic and molecular changes responsible for the development of the disease. The family of p21-activated kinases (PAKs) and especially PAK1 appears to mediate many cellular processes that contribute to the development and progression of pancreatic cancer, but the clinical relevance of PAK1 expression with the disease still remains unclear. Aim of the study was to assess the clinical value and the potential prognostic significance of PAK1 in pancreatic adenocarcinoma. Methods: We investigated the relationship between the PAK1 expression and the clinical and histopathologic characteristics of pancreatic cancer patients and the potential significance of PAK1 on survival. We examined tissue samples from 51 patients operated for pancreatic cancer. PAK1 expression was investigated with immunohistochemistry and correlated to clinicopathological parameters. Results: PAK1 was detected in all tumor samples and high expression was found in most patients. High PAK1 expression was also associated with younger age and well-differentiated tumors, but no association was found between PAK1 expression and Tumor-Node-Metastasis stage as well as deceased or alive status on follow-up. Moderate to high PAK1 expression favored higher 6-month and 1-year survival and low PAK1 expression 2-year survival but without statistical significance. Conclusions: Our results indicate that PAK1 could potentially be used as a prognostic marker in pancreatic cancer. Further studies could clarify whether utilization of PAK1 in therapeutic protocols for the treatment of pancreatic cancer will render them more effective.